THE ROLE OF THE CREATIVE WRITING COURSE AMONG STUDENTS OF THE ISLAMIC LIBRARY AND INFORMATION SCIENCE STUDY PROGRAM AT UIN RADEN INTAN LAMPUNG - Renita Cahyani Saputri; Aghesna Rahmatika Kesuma; Muhamad Bisri Mustofa (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2026)
The Creative Writing Course is one of the curriculum components with the potential to develop students' creative thinking skills, particularly in the Islamic Library and Information Science Study Program at UIN Raden Intan Lampung. This study aims to explore the role of the Creative Writing Course in developing students' creative thinking abilities. Using a qualitative approach, this research employed structured interviews with eight student informants who had completed the course. Data were analyzed using thematic analysis. The findings indicate that the Creative Writing Course significantly contributes to the development of students' creative thinking skills, as evidenced by progress across the stages of pre-writing, drafting, discussion and feedback, and revision. The recursive nature of the writing process encourages students to develop their ideas flexibly and deeply. The main obstacles faced by students include limited ideas, time management challenges, and the minimal writing culture in the academic environment. This study affirms that structured, process-based creative writing instruction can be an effective strategy for fostering creativity among library science students.